Dinâmia’CET-IUL – Activities 2013-2018 And Strategy - Costa, P.; Costa, A.; Guibentif, P. (Dinâmia’CET-IUL – Activities 2013-2018 And Strategy, 2019)
Apresentação das actividades do Dinâmia'CET 2013-2018 e plano estratégico para os próximos cinco anos.